Technology Integration in Human Resource Management and Public Sector Performance in Kaduna State, Nigeria, 2014-2023. - Abubakar, Aliyu (Mahesa Research Center, 2025)
This study assesses the impact of technology integration in human resource management HRM on public sector performance in Kaduna State, using New Public Management (NPM) theory as its theoretical framework. Primary and secondary data were collected from staff of five selected MDAs, with a Sample size of 260 drawn from a population of 770 using purposive sampling. Data were gathered through questionnaire and interviews, and analysed using descriptive and inferential statistics with SPSS. The data source ensured the generation of comprehensive and reliable information. The questionnaires were administered using a 5-point Likert scale. Interviews with some relevant stakeholders provided deeper insights, complementing the quantitative data. Data from the questionnaires were analyzed using descriptive and inferential statistics via SPSS. The findings reveal that the integration of technology in human resource management has a significant positive impact on public sector performance in Kaduna State. The study concludes that technology-driven human resource management practices enhance public sector effectiveness and recommends expanding digital human resource applications, particularly in performance appraisal and performance-linked incentives, to motivate further and improve outcomes.